GROWTH DIAMETER AND LENGTH OF ROOTS IN JELUTUNG RAWA PLANTS (DYERA POLYPHYLLA (MIQ.) STEENIS): EMPIRICAL STUDY USING FERTILIZER LIQUID WALET ACCESSION - Rahmawati R. (Russian Journal of Agricultural and Socio-Economic Sciences, 2021)
The use of swallow excretion in agriculture is no stranger, many farmers have succeeded and get maximum results with the use of swallow fertilizer, but in the field of forestry plants very rarely use swallow excretion fertilizer as a trigger for plant growth. This research was carried out for the effect of giving the best liquid swallow excretion and dose to the diameter and final length of the roots of the Jelutung Rawa (dyera polyphylla (miq.) Steenis). This study uses a randomized block design (RBD) consisting of 2 groups of observations. the first group observed open areas, the second group observed areas of shrub cover, consisting of 5 levels of treatment with 16 replications. Measurement of light intensity at the study site was done using a light-meter. Data analysis for plant diameter variables used analysis of variance for RCBD with a linear model, while for root length was done by calculating the root length ratio of each treatment. Based on the results of the study it was found that the administration of liquid swallow excretion had a significant effect to the variable increase in diameter of the Swamp Jelutung plant Rawain the open area at a level of 5% while the closed area has no significant effect. In the open area with a dose of fertilizer control and 100 gr / L produces the longest root which is 12 cm long with a long branched taproot form, while for the longest closed root area is 12.2 cm with a taproot and branched roots that are the fertilizer dose 50 gr / L.